Improvement in white light emission of Dy3+ doped CaMoO4 via Zn2+ co-doping. (1st October 2022) - Dixit, Prashant; Pandey, Prashant Kumar; Chauhan, Vaibhav; Deshmukh, Pratik; Satapathy, S; Pandey, Praveen C
Abstract: The research in developing a single ingredient phosphor for white-light emission is progressively increasing. It is well known that the 4 F9/2  →  6 H13/2 (yellow) and 4 F9/2  →  6 H15/2 (blue) transitions of Dy 3+ ions give near-white light emission. The white light emission of Dy 3+ ions can be enhanced via improving the crystallinity of the host phosphor via co-doping of transition metal ions. In this paper, we report a significant improvement in the white light emission of Dy 3+ doped CaMoO4 by co-doping Zn 2+ ions. The x-ray diffraction pattern confirms the tetragonal phase of pure and doped CaMoO4 phosphor. The peak broadening and a red-shift in the absorption peak are observed by UV–vis absorption analysis of Zn 2+ /Dy 3+ doped CaMoO4 . From Photoluminescence studies, we have observed that in Dy 3+ doped CaMoO4, the 4% Dy 3+ doped CaMoO4 exhibits maximum emission. The Zn 2+ ions are co-doped to further increase the luminescence intensity of CaMoO4 :4%Dy 3+ and the maximum luminescence is obtained for 0.25% Zn 2+ concentration. Two intense emission peaks centered at 484 nm and 574 nm related to transitions 4 F9/2  →  6 H15/2 and 4 F9/2  →  6 H13/2 of Dy 3+ ion are observed for Dy 3+ doped phosphor. The 4 F9/2  →  6 H13/2 transition is the forced electric dipole transition which is affected by its chemical environment. After Zn 2+ co-doping, the 4 F9/2  →  6 H13/2 transition is affected due to a change in asymmetricity around the Dy 3+ ions. The 0.25% co-doping of Zn 2+ gives 34% enhancement in luminescence emission of 4% Dy 3+ doped CaMoO4 . As a result, the CIE coordinates of chromaticity diagram and the color purity of the 0.25% Zn 2+ co-doped CaMoO4 :4Dy 3+ show improvement in the overall white light emission. We have shown that with Zn 2+ co-doping, the non-radiative relaxations are reduced which results in improved white light emission of Dy 3+ ions.